Decomposition of Azo Dye C.I. Direct Yellow 86 by the Fenton Process in the Presence of Nanoparticles of Iron Oxides - Kos, Lech; Sójka-Ledakowicz, Jadwiga; Michalska, Karina; Perkowski, Jan (Instytut Biopolimerów i Włókien Chemicznych (IBWCh) , Łódź, Polska, 2014)
The aim of the study was to determine the efficiency of decomposition of azo dye C.I. Direct Yellow 86 by the Fenton method in the presence of nanoparticles of iron oxides and to compare it with the classical Fenton method. Water solutions of the dye were subjected to the classical purification method with the application of ferrous sulfate and – for comparison – to a process in which iron (II,III) oxide nanopowder was added to the ferrous sulfate. Analysis of the effect of the ferrous sulfate, iron (II,III) oxide nanopowder, hydrogen peroxide and the pH of the solution on the treatment efficiency showed that the process was optimised. The use of iron oxide nanopowder increased the efficiency of dye decomposition.
Keywords: azo dye; Fenton reaction; nanoparticles; iron oxides; dye decomposition